Genome-wide identification of the GRAS gene family and evidence for the involvement of PgGRAS48 in main root development in Panax ginseng - Wang, Yihan; Wang, Ping; Di, Peng; Wang, Yingping (Frontiers in Plant Science, 2025)
Panax ginseng C. A. Meyer (ginseng) is one of the most widely used traditional Chinese medicinal herbs, with its roots as the primary medicinal part garnering significant attention due to their therapeutic potential. The GRAS [GRI (Gibberellic Acid Insensitive), RGA (Repressor of GAI-3 mutant), and SCR (Scarecrow)] genes are a class of widely distributed plant-specific transcription factors that play crucial roles in various physiological processes including root formation, fruit development, hormone signaling, and stem cell maintenance. This study systematically identified 139 GRAS genes (PgGRAS) in the ginseng genome for the first time, analyzing their complexity and diversity through protein domain structure, phylogenetic relationships, gene structure, and cis-acting element prediction. Evolutionary analysis revealed that all PgGRAS members were divided into 14 evolutionary branches, including a novel species-specific subfamily PG28, with segmental duplication being the primary driver of family expansion. RNA-seq analysis uncovered tissue-specific expression patterns of the PgGRAS gene family. qRT-PCR validation demonstrated that PgGRAS48, a member of the SCL3 subfamily, was significantly highly expressed in the main root and upregulated upon GA treatment, suggesting its potential regulatory role in main root development. Therefore, this gene was selected for further investigation. Overexpression of PgGRAS48 significantly increased the main root length in Arabidopsis thaliana (A. thaliana), accompanied by elevated endogenous GA levels. Subcellular localization, molecular docking, Bimolecular Fluorescence Complementation (BIFC) and yeast two-hybrid (Y2H) experiments confirmed the interaction between PgGRAS48 (SCL3) and PgGRAS2 (DELLA) in the nucleus, revealing the molecular mechanism by which SCL3-DELLA regulates main root elongation through gibberellin (GA) biosynthesis or signaling pathways. This study elucidates the molecular network of the GRAS family in root development in ginseng, providing key targets for the targeted improvement of root architecture in medicinal plants.